Engaged : unleashing your organization's potential through employee engagement - Holbeche, Linda (Jossey-Bass, 2012)
A non-biased, grounded, and practical approach to employee engagement For managers and business leaders who want to enhance performance, this easy-to-use guide to employee management offers real solutions for getting workers engaged and increasing productivity. It explains what employee engagement is, why it matters, what the benefits of it are, what helps and hinders it, how to measure it, how to put theory into action when trying to create it. As an added benefit, it offers plenty of advice on how managers can keep themselves engaged, even during the toughest of times. Praise.